Analisis Kualitas Produk, Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian (Study Kasus Pada Konsumen Bandung Super Model Sengkaling Malang) - Amiruddin Amiruddin; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis research is meant to find out the influence of product quality, service quality, and price to the purchasing decision at BSM (Bandung Super Model) Jl. Sengkaling Malang. The Population is all customers who have ever visited the BSM (Bandung Super Model) Jl. Sengkaling Malang. The sample collection technique has been done by using accidental sampling based on the accidental which means all customers who have ever purchased the products of BSM, and 89 respondents have been selected as samples. The data analysis technique has been done by using multiple linear regressions. The results of the test show that product quality, service quality, and price variables which have positive and significant influence to the customer decision. Based on the partial determination coefficient value, it shows that product quality becomes the variable which has dominant influence to the customer decision. It means that when the product quality is getting better, it will have influence to the increase of the customer decision at BSM (Bandung Super Model) Jl. Sengkaling Malang. Keywords: Kualitas Produk, Kualitas Pelayanan, Harga, Keputusan Pembelian.